A REVIEW OF ACCELEROMETER BASED 3D VIRTUAL GLOVE FOR ROBOT USING ARM - MS. SAVITA SHIVADAS TANDLE; PROF. R.D.PATIL (International Journal of Innovations in Engineering Research and Technology, 2021)
Weknowthe machine is desideratum of today's world. In this world we utilize different machine in different industry. Most of industrial robots are still programmed utilizing the typical technical process. In this paper is proposed an accelerometer-predicated system to control an industrial robot utilizing two low-cost and minuscule 3-axis wireless accelerometers. In this system incipient accelerometers are affixed to the human arms, capturing its demeanor (gestures and postures). An Artificial Neural Network(ANN) trained with a back-propagation algorithm was habituated to apperceive arm gestures and postures for utilize as input in the control of the robot. The aim is that the robot commences the kineticism concretely same time as the utilizer commences to perform a gesture or posture (low replication time).